Evidence-Based Practice (EBP) in the Professional Practice of Nurses - Dolega, Elżbieta; Szara, Marta; Kościołek, Aneta (Pielęgniarstwo XXI Wieku, 2024)
Aim. The purpose of this study was to analyze the application of Evidence Based Practice (EBP) in the professional practice of nurses.Material and methods. The study involved 151 active professionals in the nursing profession. The study was conducted using the diagnostic survey method, the tool was the Standardized Evidence-Based Practice Profi le Questionnaire (EBP2Q), Polish adaptation: M.Pańczyk (2017). A 5% error of inference and an associated signifi cance level of p<0.05 were assumed.Results. The lowest scores were obtained by the respondents on the subscale Frequency of use of specifi c elements of Evidence-Based Practice in daily clinical work (M=21.5 points, 47.8% of the maximum score), and on the subscale Knowledge of knowledge of research terminology (M=45.5 points, 53.5% of the maximum score). Statistically signifi cant associations were found between age, education, seniority of the subjects and the studied aspects of EBP (p<0.05).Conclusions. 1. The application of EBP in the professional practice of nurses is at a low and insufficient level. 2. Nurses present a low level of knowledge related to EBP topics. 3. Along with their younger age, higher level of education, shorter length of service of the subjects, EBP was signifi cantly more frequently used in the daily practice of the subjects.